2013
DOI: 10.1186/alzrt157
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related dementia: an update of the evidence

Abstract: The characteristics of dementia relating to excessive alcohol use have received increased research interest in recent times. In this paper, the neuropathology, nosology, epidemiology, clinical features, and neuropsychology of alcohol-related dementia (ARD) and alcohol-induced persisting amnestic syndrome (Wernicke-Korsakoff syndrome, or WKS) are reviewed. Neuropathological and imaging studies suggest that excessive and prolonged use of alcohol may lead to structural and functional damage that is permanent in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
237
1
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 243 publications
(256 citation statements)
references
References 63 publications
(116 reference statements)
2
237
1
16
Order By: Relevance
“…Although Oslin et al refined the diagnostic criteria to improve specificity by including measures of duration and severity of alcohol consumption, excluding characteristic features of Alzheimer's disease and vascular dementia and linking dementia with a minimum abstinence time before onset, 8 these criteria have yet to be validated in methodologically sound prospective studies. 4 …”
Section: Brain Damage or Dementia?mentioning
confidence: 99%
See 4 more Smart Citations
“…Although Oslin et al refined the diagnostic criteria to improve specificity by including measures of duration and severity of alcohol consumption, excluding characteristic features of Alzheimer's disease and vascular dementia and linking dementia with a minimum abstinence time before onset, 8 these criteria have yet to be validated in methodologically sound prospective studies. 4 …”
Section: Brain Damage or Dementia?mentioning
confidence: 99%
“…5 The neuropsychological profile of alcohol-related dementia has not been as well studied, but there is evidence that in comparison with Alzheimer's disease, language impairment is unlikely; with better performance on semantic tasks and on verbal memory recognition, but worse performance on visuospatial tasks. 4 However, as many also have features of WKS, there is often profound anterograde amnesia, impaired recall of past events and impaired executive functioning. 4 A UK cohort study of people with a mean age of 56 found that drinking above 32 UK units of alcohol per week was associated with greater global impairment in cognitive function, as well as in memory and executive function 10 years later.…”
Section: Brain Damage or Dementia?mentioning
confidence: 99%
See 3 more Smart Citations